2004
DOI: 10.1029/2004jd005061
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of 210Pb and 7Be in China and their analysis accompanied with global model calculations of 210Pb

Abstract: [1] Previous global models generally simulated high concentrations of 210 Pb in the surface air over China. Measured data of 210 Pb are needed in order to examine the accuracy and performance of the models. We collected the first-ever set of surface air radionuclide measurements of 210 Pb and 7 Be at Guiyang (26.57°N, 106.72°E, 1080 m above sea level) on the east of the Himalayas in Guizhou Province and at Mt. Waliguan (36.29°N, 100.90°E, 3816 m above sea level), a Global Atmosphere Watch station for the Worl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 40 publications
2
31
0
2
Order By: Relevance
“…Since pollutants cycling in the atmosphere, including residence and dispersal, are closely related to these processes, 7 Be would provide valuable insights into the pollutants cycling on a timescale corresponding to its half-life. In China, a few studies on 7 Be have been reported in several cities, i.e., Shanghai and Guizhou (Lee et al, 2004;Du et al, 2008;Kong, 2012). During the past three years, the construction and auto industry have led to heavy haze in most Chinese cities.…”
Section: Introductionmentioning
confidence: 99%
“…Since pollutants cycling in the atmosphere, including residence and dispersal, are closely related to these processes, 7 Be would provide valuable insights into the pollutants cycling on a timescale corresponding to its half-life. In China, a few studies on 7 Be have been reported in several cities, i.e., Shanghai and Guizhou (Lee et al, 2004;Du et al, 2008;Kong, 2012). During the past three years, the construction and auto industry have led to heavy haze in most Chinese cities.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the concentrations of atmospheric 222 Rn are controlled by the land-sea distribution pattern (Balkanski et al, 1992). This pattern, to a large degree, decides the longitudinal distributions of its daughters, such as 210 Pb (T 1/2 = 22.3 yr) and 210 Po (T 1/2 = 138.4 d) in the atmosphere and finally their spatial deposition patterns (Turekian et al, 1977;Lee et al, 2004). Apparently, the depositional fluxes of 210 Pb and 210 Po are latitude-dependent on a global scale (Turekian et al, 1977;Kim et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…To date, several models have been established to simulate the atmospheric 210 Pb deposition on global-scales (Turekian et al, 1977;Lee et al, 2004). However, recent researches revealed the significant intra-and inter-annual variability of 210 Pb deposition at a specific station (Su et al, 2003;Huh et al, 2006;Wan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…210 Pb activity depend on few factors that are (a) aerosol concentration [5], (b) aerosol particle size distribution [6], (c) meteorological condition and atmospheric stability [7][ 8] and (d) altitude [9]. 210 Pb has been widely used as an atmospheric tracer especially in surface air analyses for studying the atmospheric transport processes [7][10] [11]. This is because of 210 Pb characteristic which is easily absorbed onto submicrometer-sized aerosols [12].…”
Section: Introductionmentioning
confidence: 99%